PENGARUH MODEL PEMBELAJARAN VISUAL AUDITORY KINESTHETIC (VAK) TERHADAP KEAKTIFAN SISWA - Aji Setiawan Setiawan; Siti Alimah (Profesi Pendidikan Dasar, 2019)
This research is focused on the activeness of students in learning. The aim is to find out and analyze the use of cooperative learning type vak on student activeness abilities. This study uses an experimental method, a form of research Quasi Experimental Design with Nonequivalent Control Group Design models. The sampling technique was purposive sampling. In order to obtain an experimental class in the learning process using a cooperative learning model of jigsaw and a control class which in the learning process uses a direct teaching model. Data collected in the form of instruments of problem solving ability. Based on the results of data analysis, the average score of the experimental class posttest was 22.63 while the average posttest score of the control class was 17.13. Hypothesis test results using t test obtained t_count = 4.388, with dk = 30 + 32-2 = 60 and a significance level ∝ = 0.05, then t_table = 1.6706 is obtained. Thus t_count t_table which is 4.388 1.6706. Then, the effective size analysis shows the score E_s = 0.98. So it can be concluded that the use of cooperative learning model VAK type is better and more effective than the direct teaching model to increase student activity